Implementation of an Android-Based Attendance Application with Geofence Method for Employee Monitoring Efficiency - Arlan Leon Allacsta; T. Yudi Hadiwandra (International Journal of Electrical, Energy and Power System Engineering)
This research aims to develop an Android-based employee attendance application using the Geofence method at PT Wahanakarsa Swandiri. The company's main issue is the manual attendance system, which is prone to manipulation and inefficient for monitoring employee attendance, especially for those working at project locations that frequently change. This application is designed to enhance the accuracy and efficiency of attendance data collection by utilizing Geofence technology, which ensures that employees can only record attendance when they are at the designated location. In addition to the Geofence feature, the app includes QR code validation to minimize the potential for fraud. The application development methodology follows a prototype approach, starting from the communication phase to identify company needs, followed by quick design, wireframe creation, and mockups. The prototype was developed using Android Studio, with Kotlin as the programming language and PostgreSQL as the database. Application testing was conducted based on the ISO 25010 standard, covering eight aspects: functionality, reliability, efficiency, portability, maintainability, compatibility, security, and usability. The test results indicate that this application performs well in all these aspects. This application is expected to address the issues of manual attendance, improve the effectiveness of attendance data, and support more accurate company decision-making.